Tingkat Kesegaran Ikan Nila - Viky Agus Aldianto (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2021)
The purpose of this research was to identify the freshness level of some fishes based on SNI 2729-2013 regarding Fresh Fish Specifications. The research method used is a qualitative method. Data analysis was carried out using a qualitative deductive method, namely an approach by describing data from general to specific forms. The results showed that based on SNI 2729-2013, the freshness level of some tilapias (Oreochromis niloticus) that has been tested, all of those fishes relatively fresh.